An Efficient Reduction of Quinones by Formate-Palladium/Carbon System - Prakash Pande, Poorn (Asian Journal of Chemistry, 2010)
Ammonium formate in presence of palladium-carbon is an efficient system for catalytic transfer hydrogenation of several functional groups under mild conditions. However, this system was not found effective for reduction of quinones to hydroquinones, although reduction could be effected with phosphinic acid, phosphinates or cyclohexene as donors. A reexamination of this reaction suggested that formates were good hydrogen donors in this reduction but the reaction was inhibited due to quinhydrone formation. A simple expedient of maintaining low concentration of quinone during catalytic transfer hydrogenation reduction gave excellent yields of the hydroquinone. Compared to formates, formic acid was found to be a poor hydrogen donor.